2014
DOI: 10.1161/strokeaha.113.001792
|View full text |Cite
|
Sign up to set email alerts
|

Preadmission Oral Anticoagulant Treatment and Clinical Outcome Among Patients Hospitalized With Acute Stroke and Atrial Fibrillation

Abstract: Background and Purpose-Preadmission oral anticoagulant treatment (OAT) has been linked with less severe stroke and a better outcome in patients with atrial fibrillation. However, the existing studies have methodological limitations and have, with one exception, not included hemorrhagic strokes. We performed a nationwide historic follow-up study using data from population-based healthcare registries to assess the effect of preadmission OAT on stroke outcomes further. Methods-We identified 11 356 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
(48 reference statements)
1
16
0
Order By: Relevance
“…Approximately only one-third of patients with AF in our study was receiving VKAs, a rate which is in line with previous reports [14][15][16][17][18][19]27]. Notably, the CHA 2 DS 2 -VASC score prior the incident stroke was C2 in all patients with AF in our study, suggesting that all should have been on oral anticoagulants [28].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Approximately only one-third of patients with AF in our study was receiving VKAs, a rate which is in line with previous reports [14][15][16][17][18][19]27]. Notably, the CHA 2 DS 2 -VASC score prior the incident stroke was C2 in all patients with AF in our study, suggesting that all should have been on oral anticoagulants [28].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, larger studies reported smaller neurological deficit in patients with therapeutic anticoagulation at stroke onset [14][15][16][17]. Therefore, it is possible that our study did not have adequate power to reveal a beneficial effect of well-controlled treatment with warfarin on stroke severity.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations